Serum amyloid A1 promote progression of breast cancer and is associated with epithelial-mesenchymal transition - Lin, Jiali; Huang, Xiaozhi; Pan, Liuxian; Li, Mingli; Lei, Langhuan; Yang, Xing; Shi, Wei; Ding, Yanping; Jiang, Ziqiong; Li, Wei; Liang, Qiuyu (Translational Cancer Research, 2026)
Serum amyloid A1 (SAA1) is closely associated with malignant progression and unfavorable prognosis in multiple cancers. However, the specific cellular sources and mechanisms of SAA1 within the breast cancer tumor microenvironment (TME) remain incompletely understood. This study aims to investigate the SAA1 expression in the breast cancer and to elucidate its functional roles in tumor progression.